A comparison of estrogen and two different doses of calcitonin in ovariectomized rats - Kavuncu, V; Sahin, S; Baydas, G; Ilhan, N; Ozercan, I; Yasar, A; Ozercan, R (Yonsei Univ Coll Medicine, 2003)
The purpose of this study was to investigate the treatment efficacies of salmon calcitonin (SC) and estrogen in a type-I osteoporotic rat model. Sixty, 3-month-old, female Wistar rats were divided into six groups. The first group was used as the control, and the second a sham, the other four were surgically ovariectomized. 24 hours after the ovariectomy, they were either left untreated (OVX), or treated with an injection of either 17-beta estradiol (E-2) 30 mcg/kg/24 hours, low-dose calcitonin (LDC) 10 IU/kg/48 hours or high-dose calcitonin (HDC) 20 IU/kg/48 hours. 6 weeks later, the bone densities were measured by DEXA, the animals sacrificed and the femurs harvested for histomorphometric evaluation. The bone mineral densities (BMD) of the spine and proximal femur were lower in the OVX group, but only the values of the spine BMD were statistically significant. The BMD of the spine seemed to be preserved with all the treatments. The histomorphometric evaluation revealed that after the OVX the decrease in the trabecular volume was prevented by all the treatments. However, significant changes in the indices of bone formation were not shown. In conclusion, all the treatments prevented bone lost in the ovariectomized rats. Histopathological measurements of bone formation are unlikely to provide any evidence for the effects of these agents on the osteoblastic function. In the animal model of estrogen depletion, our results suggest that the calcitonin provides an important alternative therapy for postmenopausal osteoporosis.
Keywords: estrogen; calcitonin; rat